1992
DOI: 10.1007/bf01706424
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in the critically ill

Abstract: Alterations in intestinal permeability reflect one component of intestinal epithelial barrier function. The objective of this study was to assess the degree of derangement of intestinal permeability in critically ill patients and to investigate the relationship of this to markers of disease severity and sepsis. Sixteen patients admitted to the intensive care unit for a variety of problems were studied with the severity of illness and degree of sepsis recorded daily. A differential sugar absorption test, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 31 publications
3
42
0
1
Order By: Relevance
“…This is in keeping with previously published reports of permeability in critically ill patients (Harris et al, 1992). Our results suggested that LP administration had good effect on intestinal permeability of the patients with AP.…”
Section: Discussionsupporting
confidence: 93%
“…This is in keeping with previously published reports of permeability in critically ill patients (Harris et al, 1992). Our results suggested that LP administration had good effect on intestinal permeability of the patients with AP.…”
Section: Discussionsupporting
confidence: 93%
“…The importance of the gut epithelium in human health is demonstrated by the growing number of disorders that have been linked to defects in intestinal barrier function, including intestinal or extraintestinal inflammatory disorders (32,33), multiple sclerosis (34), chronic heart failure (35), cancer (36,37), and Parkinson's disease (38). In terms of mortality in humans, intestinal barrier dysfunction is reportedly common in critically ill patients and linked to development of the multiple organ dysfunction syndrome (39)(40)(41). Moreover, a chronic state of inflammation (4) and the development of insulin resistance (5) are underlying factors in a wide range of aging-related human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria can escape the IMB causing fatal syndromes [17] and BT has been linked to SIRS, acute respiratory distress syndrome and MODS [18]. Mucosal barrier permeability is increased in sepsis, trauma, burns and vascular or major abdominal surgery [19,20,21,22]. …”
Section: Bacterial Translocationmentioning
confidence: 99%